Alternatif Desain Struktur Gedung Rumah Sakit Royal 7 Lantai Surabaya Menggunakan Struktur Baja Dengan Analisis Autodesk Robot - Rian Rivaldo Markus; Bantot Sutrisno (Ge-STRAM: Jurnal Perencanaan dan Rekayasa Sipil, 2023)
The need for facilities and infrastructure is very large, one of which is the health sector. And the availability of land in the city of Surabaya is getting less and less, this is the reason why building in the city of Surabaya is built multi-story as an example in the construction of the Royal Surabaya Hospital. The construction project of the Royal Surabaya Hospital building has a building area of ±1,920 m2, consisting of 6 floors and 1 roof. In this project, it was previously designed with a reinforced concrete structure and then redesigned using a WF steel structure. In the preparation of this final project, reviewing alternative steel structure designs using seismic provisions for steel buildings SNI 7860: 2020 and calculation of deviations using Autodesk Robot structure analysis with loading referring to SNI 1726: 2019. For design purposes, a nominal load should be taken based on the load set by the loading planning guidelines for houses and buildings PPIUG 1987. Based on the results of an alternative study of the structural design of Royal Surabaya Hospital using a profile steel structure, it can be concluded as follows: From the calculation of the material price of the steel beam-column structure of Rp.7,307,850,000 and the volume of the material price of the existing concrete beam-column structure rp.8,332,012,800, it can be concluded that the steel structure is more economical than the existing concrete structure with a price difference of Rp.651,500,000 and a percentage of 8%.